JQuery pocket reference - Flanagan, David (O'Reilly Media Inc., 2011)
Presents a guide to the features of the JavaScript framework, with information on such topics as selecting and manipulating document elements, creating visual effects and animations, and scripting HTTP with Ajax utilities.